2020
DOI: 10.3390/app10155138
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Photoelectron Spectroscopy in Mineral Processing Studies

Abstract: Surface phenomena play the crucial role in the behavior of sulfide minerals in mineral processing of base and precious metal ores, including flotation, leaching, and environmental concerns. X-ray photoelectron spectroscopy (XPS) is the main experimental technique for surface characterization at present. However, there exist a number of problems related with complex composition of natural mineral systems, and instability of surface species and mineral/aqueous phase interfaces in the spectrometer vacuum. This ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 196 publications
0
7
0
Order By: Relevance
“…Similar studies have been carried out on sulfur rich systems such as pyrites and sphalerite, which until recently could not be accurately characterised in a UHV system due to the loss of sulfur species in vacuum. 146,147 Ejtemaei et al 148 combined cryo-XPS and depth profiling to study the activation of metal sulfides through the presence of Cu. Polished mineral samples were submerged in a copper sulfate solution for 10 minutes before being precooled to below À160 1C and maintained at that temperature for analysis by XPS.…”
Section: Cryo-xpsmentioning
confidence: 99%
“…Similar studies have been carried out on sulfur rich systems such as pyrites and sphalerite, which until recently could not be accurately characterised in a UHV system due to the loss of sulfur species in vacuum. 146,147 Ejtemaei et al 148 combined cryo-XPS and depth profiling to study the activation of metal sulfides through the presence of Cu. Polished mineral samples were submerged in a copper sulfate solution for 10 minutes before being precooled to below À160 1C and maintained at that temperature for analysis by XPS.…”
Section: Cryo-xpsmentioning
confidence: 99%
“…X-ray absorption spectroscopy (XANES) and some other techniques with probing depths larger than that of conventional XPS have revealed that the non-stoichiometric regions can be essentially, up to dozens and hundreds of nm thick. 25–27 We recently established, by applying synchrotron-based high energy photoemission spectroscopy (HAXPES) together with XANES and DFT+ U calculations, that the metal-deficient sulfide regions formed for the iron sulfides FeS 2 and Fe 9 S 10 (ref. 29) and chalcopyrite, CuFeS 2 , 30 in air or aqueous solutions are stratified into at least three layers (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…18 and references therein). Metal suldes undergo signicant corrosion upon contact with the atmosphere and aqueous media, which has been studied using XPS methods [12][13][14][15][17][18][19][20][21][22][23][24][25][26][27] but is still far from being completely understood. An important peculiarity of metal sulde reactivity is the preferential release of metal cations into aqueous solution or metal (hydr)oxide or/and another phase, leaving the surface and under-surface layer depleted in metal and enriched in sulfur.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations